Graphenatedtantalum(IV)oxideandpoly(4-styrenesulphonicacid)-dopedpolyanilinenanocompositeascathodematerialinanelectrochemicalcapacito - Njomo, Njagi; Waryo, Tesfaye; Masikini, Milua; Ikpo, ChinweO.; Mailu, Stephen; Tovide, Oluwakemi; Ross, Natasha; Williams, Avril (Pergamon, 2014)
Nanostructuredpoly(4-styrenesulphonicacid) and tantalum(IV)oxide-doped polyaniline nano composite were synthesized and their elector-conductive properties were determined.The oxide was synthesized using a modified sol gel method and then dispersed in acidic media through sonication and entrapped in situ in to the polymeric matrix during the oxidative chemical polymerization of aniline doped with poly(4-styrenesulphonicacid). The oxides and novel polymeric nano composite were characterised withTEM,SEM,EDX,XRD,FTIR,UV-visible to ascertain elemental and phase composition,successful polymer-ionization doping,morphology and entrapment of the metal oxide nanoparticles.The elector-conductivity of the nanomaterial was interrogated using scanning electrochemical microscopy(SECM) and cyclic voltammetry(CV).Thematerialwasthenanchoredonactivatedgraphiticcarbonandusedinthedesignofanasymmetricsupercapacitorcellusing6MKOHaqueouselectrolyte.Characteristicallyhighspe-cificcapacitancevaluesof318.4F/gwithacorrespondingenergyandpowerdensitiesof1.57kWh/kgand0.435kW/kg,respectively,were demonstrated.Thecellalsoshowedhighcoulombicefficiencyof94.9%with along cyclelife and good cyclestability making the nano material suitable for constructing super capacitor cell electrodes.
Keywords: Tantalum(IV)oxide; Polyaniline; Poly(4-styrenesulphonic)acid; Nanocomposite